CUSTOMER SATISFACTION IN GOODS AND PROCUREMENT ASSISTANCE SERVICES GOVERNMENT SECRETARIAT SERVICES REGENCY - Reza Wijaya; Trisninawati Trisninawati; Sulaiman Helmi (SEAN Institute, 2023)
This study aims to determine and analyze the level of customer satisfaction and expectations of assistance services for the procurement of goods and services at the Goods and Services Procurement Section of the Regional Secretariat of Ogan Komering Ilir Regency. In this study, researchers used quantitative and qualitative research that focused on analyzing customer satisfaction through 5 (five) dimensions of service quality, namely; Direct Evidence, Reliability, Responsiveness, Assurance and Empathy. The data has been collected by arithmetic mean and servqual gap analysis. Based on the results of the study, that overall customer satisfaction with the services provided by the Goods and Services Procurement Section of the Regional Secretariat of Ogan Komering Ilir Regency with an average value of 4.640 is in very good criteria. And customer expectations for the quality of services provided with an average value of 4.651, which is in very good criteria. Thus the servqual gap results are obtained with an average value of -0.011 which is in the medium criteria. This means that the service staff for the procurement of goods and services at the Goods and Services Procurement Section of the Regional Secretariat of Ogan Komering Ilir Regency is considered to have met the expectations or expectations for the service desired by its customers (satisfactory).